2019
DOI: 10.1016/j.cub.2019.04.017
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Competition and Cooperation within the Mammalian Gut Microbiome

Abstract: The mammalian gut harbors a vast community of microorganisms -termed the microbiotawhose composition and dynamics are considered to be critical drivers of host health. These factors depend, in part, upon the manner in which microbes interact with one another. Microbes are known to engage in a myriad of different ways, ranging from unprovoked aggression to actively feeding each other. However, the relative extent to which these different interactions occur between microbes within the gut is unclear. In this min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
177
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 213 publications
(193 citation statements)
references
References 50 publications
(71 reference statements)
3
177
0
Order By: Relevance
“…Studying this equation and its epidemiological consequences in detail, here we find that there is a critical ratio that tunes asymmetry and dynamic regimes in such multi-strain interacting system: namely the ratio of single to co-colonization. This ratio µ, given by the inverse of the product of basic reproduction number and mean permissiveness to co-colonization µ = 1/((R 0 − 1)k), increases or decreases the importance of asymmetry in interaction between strains as they encounter each-other epidemiologically in resident-co-colonizer combinations, and lends support to the context-dependence (Coyte and Rakoff-Nahoum, 2019) of relative fitnesses in a coupled microbial community. In our epidemiological system, individual strain frequency evolution over long times depends on how that strain interacts with other strains, but also on the total net interaction between extant strains.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Studying this equation and its epidemiological consequences in detail, here we find that there is a critical ratio that tunes asymmetry and dynamic regimes in such multi-strain interacting system: namely the ratio of single to co-colonization. This ratio µ, given by the inverse of the product of basic reproduction number and mean permissiveness to co-colonization µ = 1/((R 0 − 1)k), increases or decreases the importance of asymmetry in interaction between strains as they encounter each-other epidemiologically in resident-co-colonizer combinations, and lends support to the context-dependence (Coyte and Rakoff-Nahoum, 2019) of relative fitnesses in a coupled microbial community. In our epidemiological system, individual strain frequency evolution over long times depends on how that strain interacts with other strains, but also on the total net interaction between extant strains.…”
Section: Discussionmentioning
confidence: 71%
“…Theoretically, a crucial question has been to study stability and coexistence patterns in such Lotka-Volterra multi-species communities, analyzing both structured ecological networks and random networks (Serván et al, 2018). Modeling efforts seek to understand organizing principles for species composition, such as the balance between competition and cooperation (Mougi and Kondoh, 2012), which many are increasingly arguing that should be studied together in integrated and context-dependent frameworks (Bascompte, 2019;Coyte and Rakoff-Nahoum, 2019). Overall, analysis of such models with arbitrarily high dimensionality has been and continues to remain difficult.…”
Section: Introductionmentioning
confidence: 99%
“…In 2017, Ming Cui et al reported that faecal microbiota transplantation could be employed as a therapeutic to ameliorate radiation-induced toxicity and improve the prognosis of patients after radiotherapy (Cui et al, 2017). Obviously, based on current trends, understanding how the enteric microbiota affects health and disease requires a paradigm shift from focusing on individual pathogens to an ecological approach that considers the community as a whole (Coyte and Rakoff-Nahoum, 2019). Therefore, we used high-throughput 16S rDNA sequencing to examine the alterations of the gut microbiome composition after radiation exposure.…”
Section: Discussionmentioning
confidence: 99%
“…The human intestine harbours a huge number of microbes interacting intricately with each other. Previous studies have suggested that microbial interactions are not only essential for maintaining healthy ecology, but also implicated in disease-associated states [35][36][37][38][39] . In this regard, the differential microbial networks in SR and IR group may help explain the variable adaptation to the BA uctuation.…”
Section: Discussionmentioning
confidence: 99%